Sign production by first-time hearing signers: a closer look at handshape accuracy - Deborah Chen Pichler (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2009)
This paper presents phonetic analysis of hand configurations elicited from hearing adults exposed for the first time to signs in American Sign Language. The accuracy of their production is analyzed in terms of various handshape sub-features, including degree of finger splay and opposition of the thumb. Two familiar factors from spoken second language acquisition, markedness and phonological transfer, are proposed as plausible factors affecting subjects' handshape accuracy. Although these conclusions are preliminary, based only on a limited data sample, they indicate promising directions for further study of hearing adults learning a sign language as a second language. Research attention in this area stands to greatly deaf children and their parents, the vast majority of whom are hearing and need to become proficient in sign language as efficiently as possible.